The Shift to a Multipolar World: The Opportunities and Challenges this will Present to the African Union in achieving its Objectives set out in Agenda 2063 - Richardson, Liam (Université d'Ottawa | University of Ottawa, 2024)
The current international order is going through an important shift. As Western dominance declines and non-Western states such as China, Russia, India and the Gulf states see their power and influence rise, the hierarchical, American-led unipolar order is giving way to a new a new era of multipolarity. As countries strive for greater power under this multipolar order, geopolitical tensions are once again increasing as states attempt to shape the shifting international system to best reflect their preferred norms, values and institutions. This rising tension and competition are leading current and emerging powers to actively court countries across the Global South to help expand their influence and secure new partners. One of the regions that has witnessed an abundance of this attention in recent years is Africa. The renewed geopolitical competition that is becoming increasingly prevalent in the new multipolar era will undoubtedly impact the continent’s most important regional organization, the African Union (AU). As the distinct features of the bipolar and unipolar orders of the 20th and 21st century shaped the structure and functioning of the Organization of African Unity and AU, it should be expected that the new features of the multipolar international order will once again have a significant impact on the organization. However, the exact nature of this impact is still largely unknown. This paper sets out to further explore this topic through analyzing the opportunities and challenges facing the AU in achieving the objectives set out in its Agenda 2063 document in the context of the current multipolar shift of the international order. Specifically, the paper focuses on the impact of two objectives that are pinnacle to the AU achieving its Agenda 2063 and broader Pan-African objectives. These objectives are: (1) An Africa of good governance, democracy, respect for human rights, justice and the rule of law and (2) Africa as a strong, united, resilient, and influential global player and partner. Through conducting an extensive analysis of both primary and secondary documents and research, the paper argues that while the new era of multipolarity could provide the AU with greater power and leverage in international politics, it could also further divide the continent while eroding democratic and liberal values that are cornerstone to the AU. Recognizing these opportunities and challenges highlights that the shift to a multipolar has placed the AU at a critical point in time. On one hand, a multipolar world could allow the AU to secure greater influence in international relations through leading a united African continent on the international stage. However, multipolarity could also undermine the power of the organization through dividing the continent into competing factions as African states choose to prioritize national policies and sovereignty at the expense of greater continental unity. Should this occur, the chance of achieving its Agenda 2063 objectives becomes virtually impossible. Keywords: African Union, Africa, Multipolarity, Global Governance